The Role Of Brand Awareness In Influencing Purchase Intention In The Manufacturing Sector - SEGUN KEHINDE (International Journal of Economics, Business and Innovation Research, 2025)
This study delves into the integral role of brand awareness in shaping purchase intention within the manufacturing sector. Brand awareness stands as a pivotal factor in influencing consumer choices and purchase decisions. This research investigates the depth of its impact on consumer behavior, focusing on its role in increasing trust, recognition, and favorability of specific brands. Through a comprehensive analysis of the manufacturing sector, using both quantitative and qualitative methods, this study offers insights into the dynamic interplay between brand awareness and purchase intention. The findings illuminate the profound influence brand awareness wields in the context of consumers' purchasing decisions and choices. The implications of this research extend to marketing professionals, business leaders, and scholars, providing a deeper comprehension of the critical relationship between brand awareness and consumer behavior. Recognizing the significant role of brand awareness enables organizations to make informed branding decisions that resonate with their target audience, fostering increased purchase intention and market success.